FUZZY LOGIC APPROACH FOR POST-MINING LAND USE PLANNING: A CASE STUDY ON COAL MINE OF PT. ADARO INDONESIA-SOUTH KALIMANTAN - Mohamad Anis; Arifudin Idrus; Hendra Amijaya; Subagyo Subagyo (Puslitbang tekMIRA, 2017)
Currently coal companies, especially in South Kalimantan, have not yet been or only slightly entered the post-mining stage, although part of the mining blocks have been totally exploited, so that the company should have been preparing for the development of other sectors (non-mining). It shows that optimization of coal resources from exploration, mining to post-mining land use is necessary to ensure sustainable mining and sustainable development in terms of meeting the conservation aspect. To meet all aspects of conservation, the achievement of optimization in a series of mining business activities is started from the potential optimization of the coal remain resources until the optimization of post-mining land use is absolutely required. This research has analyzed several alternative sectors outside mining, which will be selected for optimization of utilization or post-mining land use, including plantation, recreation, industry and conservation sectors. The analyzing process used several parameters to assess the selected sectors including rainfall, slope and land use. Therefore, this study uses an approach of GIS-based methods (knowledge-driven), mainly fuzzy logic for post-mining land use planning. The selected mining area for this study belongs to PT. Adaro Indonesia company that has a Work Agreement for Coal Mining Exploitation. The result shows the suitability of plantation for the optimization of land use in all mining sites and also for conservation areas or protected forests.